Elite female tissue culture papaya ‘Dawn Delight’ - Thomas, Pious (Indian Horticulture, 2023)
Papaya is generally propagated using seeds where the seedling population could segregate into female, male, and hermaphrodite plants depending on the genetic background of the parental line. Tissue culture allows the selective rapid multiplication of desired plants and preferred sex forms. An elite papaya line ‘Dawn Delight’ has been identified and is now clonally multiplied through tissue culture. ‘Dawn Delight’ consists of only female plants with the parthenocarpic fruit setting which avoids the need for the pollinizer male or hermaphrodite plants. In the absence of pollination, fruits become seedless displaying very slow ripening with extended keeping quality of 38 days. Fruits are ovoid-oblong, medium size, weighing about 1.0 kg±250 g. ‘Dawn Delight’ offers a uniform field stand of dwarf female plants with continuous bearing and higher yields. Seedless fruits with extended keeping quality and firm red flesh add brand value and e xport potential for this line. ‘Dawn Delight’ forms an ideal candidate for terrace cultivation due to its dwarf stature. Although micropropagation of papaya has been reported in literature decades ago, commercial multiplication through tissue culture is demonstrated for the first time in this country.